Investigation of thermal and technological characteristics of new meat pastes production - Moskalyuk, Oksana; Chernyushok, Olga; Fedorov, Volodumer; Kepko, Oleg; Zhurilo, Svitlana (Technology audit and production reserves, 2018)
The object of research is the thermal and technological characteristics of the production of meat pastes, namely, chicken meat and liver patties, as a delicious, nutritious (assimilated by 94–96 %) and at the same time low-calorie product. One of the most problematic places is the quality management of the process of designing functional food products, taking into account their intended purpose. The creation of meat products on the basis of the combination of meat and vegetable raw materials is one of the effective ways of solving the problem of balanced nutrition, regulation of properties and optimization of biological value of the finished product. The article presents the research of developed pest recipes for the naturally-appropriate health and prophylactic nutrition of high biological value. This gives an opportunity to expand the range of meat products, to enrich the daily ration with useful infusions and food fibers, which promote the health, efficiency and active creative longevity of man. During the study methods of organoleptic, physico-chemical, functional-technological and structural-mechanical research were used. To determine the optimal amount of the proposed ingredients, a study was made of their effect on the organoleptic and functional and technological parameters of the model combined systems. Components of new pastes and finished products undergo a different thermal (heat or refrigeration) treatment. The individual components of the minced meat are pre-cooled or frozen, others are cooked or blanched, the prepared minced meat is sterilized in tinplate, roasted in metallic forms or cooked in a vapor mixture or hot water. The finished product is cooled. The paper presents the results of the study of thermal load changes during the heat treatment of pieces of meat products. These data are obtained by direct measurement of the heat flux density by means of small-scale inertial heat measurements that do not interfere with the flow of the technological process. The results of the organoleptic evaluation of model products show their pleasant taste and aroma, uniform, delicate, greasy consistency. This makes it possible to recommend for mass production three developed formulations of the «Mushroom», «Spicy» and «Special» pastes.